A Decision Support Tool for Classification of Turkish SMEs’ Industry 4.0 Score Levels - Dündar, Uğurcan; YÜKSEKTEPE, FADİME ÜNEY; GERGİN, ZEYNEP; EMİR, OĞUZ; Gençyılmaz, Güneş M.; Çavdarlı, Ali İhsan (Springer Science and Business Media Deutschland GmbH, 2021)
The concept of industry 4.0 aims to enhance the employment of digitalization with the help of burst in computer usage after the third major revolution in industry. Hence, to keep up with the new trends in industry, companies should transform their processes into digital platforms. In Turkey, 99.8% of the companies are SMEs, so in order to be in the global economic competition Turkey should enable their SMEs to make the process shifts to digitalization. In this manner, in 2018 a project is initiated by KOSGEB to evaluate the readiness of SMEs and help them for Industry 4.0. As the last step of this project, a decision support tool is created with classification algorithm behind. In this paper, chosen instruments are used to predict the Industry 4.0 score of SMEs that are calculated with previously published algorithm in the scope of the project. In terms of classification, three algorithms are compared with ROC metric. CatBoost algorithm which is specifically created for categorical classification is compared with Support Vector Machine algorithms (SVM and µ-SVM) that performed best in previous research. CatBoost outperformed other algorithms and is used as base classification method in decision support tool. This decision support tool will be used in decision making process of KOSGEB to which companies to help. © 2021, The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG.
▪ International Symposium for Production Research, ISPR 2020, Antalya, 24 September 2020through 26 September 2020. ▪Part of the Lecture Notes in Mechanical Engineering book series (LNME).
Keywords: Catboost; Data Classification; Decision Support Tool; Industry 4.0; Small and Medium Enterprises; Support Vector Machines